Program of Visual Inspection with Acetic Acid for Women of Childbearing Age Based on Healthcare Service Accessibility - Yetti, Husna; Simarmata, Sondang; Ramadani, Mery (Newinera Publisher, 2025)
According to Globocan data, in 2022, cervical cancer caused 348,874 deaths among women, and cases of cervical cancer in Indonesia increased to 36,633 people. WHO recommends early detection through the VIA (Visual Inspection with Acetic Acid) examination. However, the VIA examination coverage in Kampar Regency in 2023 was low, at only 1.2%. This study aims to analyze the Acetic Acid Visual Inspection (VIA) program for women of reproductive age (WRA) based on healthcare service accessibility in Kampar Regency, Riau Province, in 2024. This research uses a cross-sectional method, and the results show that information about VIA services is lacking, the acceptance of VIA services is low, service hours are not always available, and community empowerment in supporting VIA services is insufficient. The factors that most influence the participation of women of reproductive age in the VIA examination, based on healthcare service accessibility, are service acceptance (p=0.008 and exp(B)= 19.342) and community empowerment (p=0.017 and exp(B) = 8.272). Variables such as service location distance, knowledge, attitude, transportation ease, and environmental support did not significantly affect the situation. It is recommended that service acceptance be improved through promotion, education, and service socialization, as well as strengthened community empowerment by involving local health workers, the Family Welfare Movement (PKK), and related cross-sector stakeholders in an integrated manner.